2021
DOI: 10.24815/siele.v8i2.18562
|View full text |Cite
|
Sign up to set email alerts
|

Developing descriptive reading materials in EFL classes by utilizing the local culture

Abstract: This study aimed to develop instructional descriptive reading materials of Bangka local culture in Indonesia, which are valid, practical and have a potential effect for Tour and Travel Study Program students at a vocational school in Bangka Belitung Province. The developed product would be used as supplementary materials to fulfill the students’ needs. This study used the research design proposed by Akker (1999), covering the phases of analysis, design, evaluation, and revision modified by Tessmer (1993). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 22 publications
(49 reference statements)
2
12
0
Order By: Relevance
“…For example, Elviana et al (2020) focused on Palembang local culture descriptive texts-based interactive multimedia development for teaching. Likewise, Herawati et al (2020) developed the Islamic instructional descriptive reading material for the seventh grader, while Azizah et al (2021) developed the reading materials of descriptive texts in English classes by the utilization of local culture. The finding of those studies revealed that (1) some local cultures used to produce the reading material, and (2) the development of reading material had high validity, practicality, and effectivity.…”
Section: Materials Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Elviana et al (2020) focused on Palembang local culture descriptive texts-based interactive multimedia development for teaching. Likewise, Herawati et al (2020) developed the Islamic instructional descriptive reading material for the seventh grader, while Azizah et al (2021) developed the reading materials of descriptive texts in English classes by the utilization of local culture. The finding of those studies revealed that (1) some local cultures used to produce the reading material, and (2) the development of reading material had high validity, practicality, and effectivity.…”
Section: Materials Developmentmentioning
confidence: 99%
“…It is a type of recount text that serves as a vehicle for presenting an imaginative story (Mediska & Adnan, 2019). Most reading genres taught to learners, particularly in vocational high schools, are descriptive texts (Azizah et al, 2021). The recount text is rarely used as essential reading material by teachers.…”
Section: Recount Textmentioning
confidence: 99%
See 2 more Smart Citations
“…In language learning, local culture is important to raise awareness of the students' community and socialize with global citizens has been investigated by some previous researchers (Azizah, et al, 2021;Kumbara, et al, 2021;Inderawati, et al, 2021;Inderawati, et al, 2018). In other Rita Inderawati, et.…”
Section: Local Culture In Language Learningmentioning
confidence: 99%